Pelaksanaan Sistem Informasi Pemantauan Status Gizi (Psg) Balita Di Dinas Kesehatan Kabupaten Boyolali - Widyaningrum, Agustin (2016)
Information about nutritional status of toddlers is one of indicators assessment degrees community health. To find out information about the nutritional status of toddler there needs to be monitoring the nutritional status (PSG) toddlers. Toddler nutrition status information is also needed to determine policy by decision makers, thus needed a good information system. PSG activities toddler in Boyolali district health service is still done with the conventional way and have yet to implement a SMS Gateway. The purpose of this research is to understand the implementation of information system monitoring the nutritional status (PSG) toddler in district health offices Boyolali. The research is qualitative study. Informants in this research consisting of 6 informants main and 1 informant triangulation. The determination of informants this research used technique purposive sampling.Data collection carried out by interviews directly to informants. Analysis of data in this research using reduction data, presentation of data, and the withdrawal of conclusion. The result showed that the information system PSG toddler in district health offices Boyolali already done well although found a number of problems in practice. Obstacles of them incompleteness data, unaccurate data, and the problem of timeliness of reporting. In addition, obstacles found in PSG toddler in district Boyolali is there has never been a map distribution nutrition. Keywords: Informations System, Monitoring the Nutritional Status (PSG) toddlers, District Health Offices Boyolali